Factors Affecting the Level of Hemoglobin on Junior High School Children on Coast Regional District of North Lombok - Nurdiana Nurdiana (Universitas Islam Negeri Mataram, 2015)
Hemoglobin is the number of hemoglobin ain red blood cells that assessed in grams per decilitre. One of the problems in the hemoglobin is anemia. The prevalence of anemia in junior high school students aged 10-14 years old at 57.1%. anemia is caused by a decrease in hemoglobin levels. These levels can change at any time depending on various factors, especially in junior high school students who are still in its infancy. Therefore, the researchers wanted to know what are the factors that effect hemoglobin levels were in junior high school students in Nort Lombok region. The sampling technique was aconsecutive sampling, which any student who meets the study inclusion an exclusion criteria included in the study until acertain time, so that the required number of students are met. Data retrieval was done by using research instruments such as questionnaires, complete blood count, and anthropometric examination. Statistical analysis using descriptive analysis, bivariate analysis using spearmans, and multivariate analysis using linear regression to test the strength of each risk factor. The results showed there was one factor that effects the hemoglobin level in junior high school students on coast regional district of Nort Lombok. This factor was diet.